2019
DOI: 10.1109/tits.2018.2882565
|View full text |Cite
|
Sign up to set email alerts
|

Subsampling OFDM-Based Ultrasonic Data Communication Through Metallic Channels for Monitoring of Cargo Containers

Abstract: An enhanced ultrasonic communication system based on piezoelectric transducers for monitoring of goods in cargo containers is presented. The proposed system consists of several sensors placed inside the container, whose data are collected and transmitted outside it. Data transmission is carried out by an ultrasonic communication channel, in order to avoid drilling the wall of the container. The proposed data communication system is based on the transmission of a 128-OFDM signal. This modulation has been chosen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…The OFDM technique divides the frequencyselective channel into orthogonal flat fading bands, allowing for a marked increase in data rate without using highly complex equalizers to correct signal fading. Previous literature indicated that OFDM-based communications could accomplish high-data-rate transmission through metal barriers [20][21][22]; however, one shortcoming of OFDM is that it will result in a high peak-to-average power ratio (PAPR). High PAPR means that the system should consume high power and employ a power amplifier with a broad linear range for the transmitter.…”
Section: Introductionmentioning
confidence: 99%
“…The OFDM technique divides the frequencyselective channel into orthogonal flat fading bands, allowing for a marked increase in data rate without using highly complex equalizers to correct signal fading. Previous literature indicated that OFDM-based communications could accomplish high-data-rate transmission through metal barriers [20][21][22]; however, one shortcoming of OFDM is that it will result in a high peak-to-average power ratio (PAPR). High PAPR means that the system should consume high power and employ a power amplifier with a broad linear range for the transmitter.…”
Section: Introductionmentioning
confidence: 99%